2017
DOI: 10.1292/jvms.16-0531
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of the transcriptome in the anterior pituitary of heifers before and after ovulation

Abstract: We aimed to determine gene expression patterns in the anterior pituitary (AP) of heifers before and after ovulation via deep sequencing of the transcriptome (RNA-seq) to identify new genes and clarify important pathways. Heifers were slaughtered on the estrus day (pre-ovulation; n=5) or 3 days after ovulation (post-ovulation; n=5) for AP collection. We randomly selected 4 pre-ovulation and 4 post-ovulation APs, and the ribosomal RNA-depleted poly (A)+RNA were prepared to assemble next-generation sequencing lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, in our study, we found lncRNA MSTRG.9440.3 target GPR61 , SORT1 , SYPL2 and PSMA5 in sheep pituitary gland. Previous studies suggested that GPR61 has a different expression in the pre- and post-ovulation of bovine anterior pituitary [ 62 ]. Although the ligand(s) and functions of GPR61 are not clear, it is known to associate with the Gs protein and stimulate extracellular regulated protein kinases ( ERK ) signaling in neurons [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our study, we found lncRNA MSTRG.9440.3 target GPR61 , SORT1 , SYPL2 and PSMA5 in sheep pituitary gland. Previous studies suggested that GPR61 has a different expression in the pre- and post-ovulation of bovine anterior pituitary [ 62 ]. Although the ligand(s) and functions of GPR61 are not clear, it is known to associate with the Gs protein and stimulate extracellular regulated protein kinases ( ERK ) signaling in neurons [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…After emulsion PCR was performed using 0.7 pM of DNA library, the emulsions were broken and the beads attaching the amplified DNA were collected. Approximately 280 million beads per lane were applied to the flowchip in a SOLiD5500 (Thermo Fisher Scientific) 41 .…”
Section: Methodsmentioning
confidence: 99%
“…My previous deep transcriptome sequencing studies in heifer AP before and after ovulation did not reveal significant differences in the expression of AMHR2, the receptor for AMH [40]. AMH is a dimeric glycoprotein belonging to the transforming growth factor (TGF)-β family and it is primarily produced by the granulosa cells of the preantral and small antral follicles in humans and animals [51].…”
Section: Bovine Gonadotrophs Express Amhr2 and Amh To Regulate Lh Andmentioning
confidence: 99%
“…Therefore, I assessed gene expression patterns via RNA-seq in the AP, but not in the purified gonadotrophs of heifers before and after ovulation [40]. Consequently, 396 differentially expressed genes were identified in the bovine AP (P < 0.05) in pre-and post-ovulation samples, which included two GPCR genes (GPR61 and GPR153), and nine receptors for previously identified ligands.…”
Section: Deep Transcriptome Sequencing Of the Ap Of Heifers Before Anmentioning
confidence: 99%